Challenges and prospects of ESG reporting: analysis of theoretical and practical aspects - O.V. Oliinyk; D.M. Zakharov (Економіка, управління та адміністрування)
ESG reporting has become a critical component of corporate transparency, driven by growing stakeholder demands and changing regulatory requirements. The article identifies critical problems, including the need for standardized reporting systems, the complexity of data collection, and the diversity of regulatory and legal acts in different countries. In addition, the article examines the theoretical foundations of ESG reporting: stakeholder theory, legitimacy theory, and signaling theory. The theoretical foundations emphasize the importance of aligning corporate practices with the expectations of a wide range of stakeholders. The paper examines industry practices and geographic differences in ESG reporting practices, highlighting how different sectors and regions prioritize different aspects of ESG performance. Despite the challenges, the paper argues that the future of ESG reporting is promising. The spread of ESG reporting practices depends on the support of global initiatives to harmonize reporting standards and the growing recognition of the importance of sustainable development. By addressing these challenges, companies can improve their ESG performance, contribute to sustainable development, and strengthen stakeholder relationships. The article provides a comprehensive analysis of the current state of ESG reporting and offers insight into its future direction. The research was carried out with the support of the Ministry of Education and Science of Ukraine within the framework of the project «Development of a Mechanism for Sustainable Development of Economic Systems in the Conditions of Military Actions and Post-War Economic Recovery» (registration number 0124U000463).